Well-Organized Inorganic Nanowire Films : Assemblies and Functionalities - Liu, Jian-Wei (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2017)
This thesis presents the latest findings on macroscopic-scale nanowire thin ﬁlms composed of integrated nanowires. It introduces readers to essential synthesis and assembly strategies for the design and fabrication of high-quality nanowire thin films, and discusses their underlying principles in detail. The book highlights examples specific to well-aligned nanowire systems, and explores the applications of nanowire systems, including memory devices, flexible transparent electrodes, etc. The book offers a valuable resource for researchers and graduate students working in materials science, especially in nanowire device fabrication.